2020
DOI: 10.1111/anae.15215
|View full text |Cite
|
Sign up to set email alerts
|

The effect of trimodal prehabilitation on the physical and psychological health of patients undergoing colorectal surgery: a randomised clinical trial

Abstract: Prehabilitation aims to increase the endurance capacity of patients who are awaiting major surgery. However, there are no studies investigating the implementation of this demanding and expensive intervention in lowincome countries. This study aimed to assess the impact of a 4-week trimodal prehabilitation program on the physical and psychological health of patients waiting for colorectal surgery compared with a control group managed according to enhanced recovery after surgery principles supplemented by nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
98
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(110 citation statements)
references
References 28 publications
0
98
0
Order By: Relevance
“…These could cause a delay of postoperative chemotherapy and have a detrimental effect on the oncological outcome 27,28 . It has been shown by previous studies that exercise and personalized prehabilitation could lower the postoperative complication rate significantly 29 . However, regarding hepato‐pancreato‐biliary surgery, only a few articles provide information about prehabilitation, 14,30–33 which suggest an average of 4‐6 weeks of exercise consisting of walking or light physical exercise adjusted to the patient's initial condition.…”
Section: Discussionmentioning
confidence: 99%
“…These could cause a delay of postoperative chemotherapy and have a detrimental effect on the oncological outcome 27,28 . It has been shown by previous studies that exercise and personalized prehabilitation could lower the postoperative complication rate significantly 29 . However, regarding hepato‐pancreato‐biliary surgery, only a few articles provide information about prehabilitation, 14,30–33 which suggest an average of 4‐6 weeks of exercise consisting of walking or light physical exercise adjusted to the patient's initial condition.…”
Section: Discussionmentioning
confidence: 99%
“…There has been much interest in the past few years concerning frail patients and post-operative outcomes (33), with studies comparing frailty scores as outcome markers (8)(9)(10). Several studies examining prehabilitation in elderly colorectal patients have been conducted in metropolitan centres in Canada (19,23,34), the United Kingdom (35), Hungary (21), and a regional hospital in the Netherlands (12). These studies have demonstrated improved post-operative functional walking capacity (19,21), and return to baseline exercise capacity after neoadjuvant chemoradiotherapy (35).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies examining prehabilitation in elderly colorectal patients have been conducted in metropolitan centres in Canada (19,23,34), the United Kingdom (35), Hungary (21), and a regional hospital in the Netherlands (12). These studies have demonstrated improved post-operative functional walking capacity (19,21), and return to baseline exercise capacity after neoadjuvant chemoradiotherapy (35). Chia and colleagues (20) highlighted the potential of prehabilitation for frail colorectal patients with a ∼2.5-day shorter hospital stay following a novel trans-institutional, transdisciplinary model of care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations